Integrated Information System of Material Resource Planning and Supply Chain Procurement: A Case Study of XYZ Company - Santo Wijaya; Marta Hayu Raras Sita Rukmika Sari; Yeyeh Supriatna (Bina Nusantara University, 2022)
Human errors are inevitable due to the mass customization and complex supply chain, which must be considered in the Material Resource Planning (MRP) explosion calculation and the Supply Chain Procurement (SCP) distribution of sales orders. Such errors lead to SCP problems with the subject company. The research presents the design and implementation of an integrated information system of MRP and SCP. The objective is to solve the issues in the subject company by designing and implementing an Integrated Information System (IIS) framework with an open-source software platform, which utilizes a generic Bill-of-Materials (BoM) explosion algorithm to calculate the MRP of customers’ sales orders. Then, an algorithm is also proposed to calculate SCP distribution to enable the framework in the implementation stage. The research subject is the process business in Indonesia’s local Original Equipment Manufacturer (OEM) for automotive components. The name of the company is concealed to be XYZ Company. The calculation is introduced in the testing phase to illustrate the algorithm’s mechanism. This approach ensures a valid calculation of efficient supply chain processes. The combined approaches in the subjected business process yield satisfactory results. It reduces significant issues to 12.5% for the stated problems. Hence, the design objective is achieved.